Analytical and Experimental Study of Load-bearing Beams Made of Lightweight Concrete (Journal of Civil Engineering Researchers, 2022)
In recent years, the use of lightweight concrete in the world has grown exponentially. The reason is the lightening of the buildingand as a result the reduction of dead load and seismic force on the structures as well as better performance in terms of thermalinsulation and energy saving. Therefore, it is necessary to study the potentials of using lightweight concrete in the constructionindustry. In this article, which is the result of analytical and experimental results about a special type of lightweight aggregatecalled Leica, the aim is to first achieve a lightweight concrete mixing design that has the necessary conditions as lightweightstructural concrete. In this paper, during laboratory research, using Leica concrete grain style with an approximate compressivestrength of 20 MPa and a specific gravity of approximately 1800 kg / m3 was obtained. Secondly, we investigated the structuralbehavior of concrete beams made with Leica lightweight aggregate experimentally and numerically. For this purpose, the first 5concrete beams were made and examined in the laboratory, and finally, using ABAQUS finite element software, a suitable modelwas found to model such beams, which is in good coordination with the laboratory results. The compatibility of the resultsobtained from the modeling with the laboratory results is proof of the accuracy of the constructed model.
Keywords: Lightweight concrete beam; Finite element analysis; Laboratory study; Bending behavior of beams; ABAQUS